Building Security in the Persian Gulf - Hunter, Robert E. (RAND Corporation, 2010)
The United States must determine how best to promote long-term security and stability in the Persian Gulf region while seeking to reduce the risks and costs imposed by its role as a permanent regional power. The author analyzes Iraq's future, the role of Iran, asymmetric threats, regional reassurance, regional tensions, and the roles of other external actors. He then sets out criteria and requirements for a new regional security structure.